2023
DOI: 10.2478/jofnem-2023-0056
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification of entomopathogenic nematodes with insights into their distribution in the Syrian coast regions and virulence against Tuta absoluta

Mai Ali,
Nada Allouf,
Mohammad Ahmad

Abstract: The occurrence and distribution of entomopathogenic nematodes (EPNs) in the Syrian coast regions remain relatively uncharted. To address this gap in our knowledge, an extensive survey of these ecosystems was essential. This study aims to isolate and identify EPNs from diverse ecosystems within the coastal regions. The distribution of EPNs in cultivated and natural environments was analyzed according to habitat, altitude, and sampling season factors. Between 2017 and 2020, EPNs were recovered from 27 out of 821… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Surveys in specific habitats with a higher prevalence of EPN generally achieve a greater recovery compared to non-targeted surveys (Mráček & Bečvář, 2000). In addition, seasons are known to strongly affect the distribution and occurrence of EPN (Ali et al, 2023;Půža & Mráček, 2005). Low EPN recovery in this study may be caused by the soil samples collected during late November to February which are the end of the rainy season in Thailand.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Surveys in specific habitats with a higher prevalence of EPN generally achieve a greater recovery compared to non-targeted surveys (Mráček & Bečvář, 2000). In addition, seasons are known to strongly affect the distribution and occurrence of EPN (Ali et al, 2023;Půža & Mráček, 2005). Low EPN recovery in this study may be caused by the soil samples collected during late November to February which are the end of the rainy season in Thailand.…”
Section: Discussionmentioning
confidence: 76%
“…Low EPN recovery in this study may be caused by the soil samples collected during late November to February which are the end of the rainy season in Thailand. Many studies showed that high EPN prevalence was found in the spring and autumn seasons, while the EPN populations declined during the dry season (Ali et al, 2023;Campos-Herrera et al, 2010).…”
Section: Discussionmentioning
confidence: 99%